Rising Tide of Antibiotic Resistance in Sub-Saharan Africa: A Meta-Analysis of Vibrio cholerae Susceptibility(2014-2024) - Dr Yahaya Mohammed; Dr Ahmed Olowo-okere (International Journal of Infectious Diseases)
Introduction: Antibiotics are commonly used alongside rehydration therapy in the management of cholera. Their efficacy is however increasingly compromised by global rise of antibiotic-resistant bacteria. This is particularly concerning in sub-Saharan Africa, where cholera is endemic, recurrent and access to effective antibiotics is highly limited. This study aims to systematically evaluate data on antibiotic resistance in Vibrio cholerae isolates across sub-Saharan Africa. Methods: We conducted a systematic literature search across PubMed, Scopus, Embase, Google scholar and Web of Science databases to identify articles reporting the susceptibility profiles of Vibrio cholerae isolates from cholera patients between 2014 and April 2024. We utilized the Freeman-Tukey double arcsine transformation to estimate the weighted pooled resistance (WPR). Heterogeneity of the data and bias were analyzed with random effect model meta-analysis and funnel plot. The data were analyzed using Comprehensive Meta-Analysis Software Version 4.0 (Biostat, Englewood, NJ, USA) Results: This meta-analysis presents results of antibiotics resistance profile of 1761 V. cholerae isolates from 12 countries. The isolates were predominantly O1 El tor serogroup with 71.2% ogawa and 28.8% inaba biotypes. Majority of the studies were from Nigeria (6/22) followed by Ghana (4/22) and Kenya (3/22). Ciprofloxacin (19/22), tetracycline (18/22) and trimethoprim-sulfamethoxazole (17/22) were the most frequently studied antibiotics. The results revealed varying rates of resistance among different antibiotics, with co-trimoxazole 77.99% (C.I.: 0.6702-0.8606) exhibiting the highest resistance, followed by nalidixic acid 67.25 % (C.I.: 0.4625-0.8305) and amoxicillin-clavulanate 74.91 % (C.I.: 0.411- 0.927). The WPR of tetracycline, ciprofloxacin and chloramphenicol were respectively 29.74 % (C.I.: 0.1912-0.4313), 8.41% (C.I.: 0.0423-0.1605) and 32.71 % (0.1708-0.5343). Regional analysis revealed that WPR of tetracycline and ciprofloxacin were highest in Nigeria (60.75 %) and Zambia (59.04 %) respectively. The WPR for tetracycline and ciprofloxacin increased notably after 2020 COVID-19 pandemic, rising from 16.6% (0.0687-0.3499) to 39.1% (0.2314-0.5784) and from 1.5% (0.0042-0.0552) to 16.2% (0.0802-0.2990), respectively. This upward trend was also observed across other antibiotics studied. Discussion: The meta-analysis reveals a worrying rise in antibiotic resistance among V. cholerae in sub-Saharan Africa. The increasing antibiotic resistance observed both before and after 2020 could potentially be associated with the global rise in antibiotic resistance, possibly stemming from the overuse of antibiotics during the COVID-19 pandemic. Conclusion: The findings underscore the alarming prevalence of antibiotic resistance among V. cholerae isolates in sub-Saharan Africa. We also noted a lack of data on V. cholerae susceptibility in several countries. With high rates of resistance observed against commonly used antibiotics, the effectiveness of current treatment regimens for cholera is severely compromised. Urgent measures such as enhanced surveillance, judicious antibiotic use, and implementation of antibiotic stewardship are thus urgently needed to address this growing public health threat in the region.